KUMULASI GUGATAN PERBUATAN MELAWAN HUKUM DAN GUGATAN WANPRESTASI DALAM KAJIAN HUKUM ACARA PERDATA DI INDONESIA - Rai Mantili; Sutanto Sutanto (Faculty of Law, Maranatha Christian University, 2019)
This article describes the integration of lawsuits in breach of law or breach of contract which often found in court examination practice. First issue will analyze whether the integration of lawsuits can be conducted between breach of law and breach of contract claims pursuant to Indonesian Civil Procedures. The second issue will analyze the legal consideration of judges who reject the integration of lawsuits between breach of law and breach of contract claims pursuant to Indonesian Civil Procedures There are some of opinions of judges or expert against the integration of lawsuits between breach of law and breach of contract claims. A jurisprudence states that the integration of lawsuit between breach of law and breach of contract claim in lawsuit is violating the code of conduct since both shall be examined respectively. HIR, RBG and RV does not strictly stipulate and prohibit the integration of lawsuit, however, pursuant to Jurisprudence of The Supreme Court of the Republic of Indonesia No. 1875K/Pdt/1984 dated April 24, 1986, “the integration of lawsuits between the breach of law and breach of contract claims cannot be conducted since it is violating the civil procedures and accordingly it shall be examined respectively. In accordance with such jurisprudence, the Judex Jurist is authorized to declare that the integration of lawsuits between the breach of law and breach of contract claims is unacceptable lawsuit (NO/niet oontvankelijk verklaard).